The Correlation Between Estimated Glucose Disposal Rate and Coagulation Indexes in Type 2 Diabetes Mellitus - Li Z; Qi C; Jia Z; Zhen R; Ren L; Jia Y; Chen S (Diabetes, Metabolic Syndrome and Obesity, 2022)
Zelin Li,1,2 Cuijuan Qi,1 Zhuoya Jia,1,2 Ruoxi Zhen,1,2 Lin Ren,1,3 Yujiao Jia,1,2 Shuchun Chen1,2,4 1Graduate School of Hebei Medical University, People’s Republic of China; 2Department of Endocrinology, Hebei General Hospital, People’s Republic of China; 3North China University of Science and Technology, People’s Republic of China; 4Hebei Key Laboratory of Metabolic Diseases, People’s Republic of ChinaCorrespondence: Shuchun Chen, Department of Endocrinology, Hebei General Hospital, 348 Heping West Road, 050051, People’s Republic of China, Tel +86 031185988406, Fax +86 031185988406, Email chenshuc2014@163.comPurpose: To study the correlation between estimated glucose disposition rate (eGDR) and coagulation parameters in type 2 diabetes patients (T2DM).Materials and Methods: A total of 948 patients suffering from T2DM were enrolled for this research. Various blood coagulation parameters including prothrombin time (PT), activated partial thromboplastin time (APTT), and fibrinogen (FIB) were assessed. Body mass index (BMI), hypertension, and the levels of glycated hemoglobin (HbA1c) were used to calculate the patients’ eGDRs. All patients were sorted into two groups: those with high eGDRs (eGDR≥ 7.5) and those with low eGDRs (eGDR< 7.5). The patients were then separated into groups of men and women. The connection between eGDR and coagulation indexes was examined using Spearman correlation, Pearson correlation, and multiple linear regression analysis.Results: In comparison to the high-eGDR group, reduced PT and APTT levels with increased FIB levels were observed in the low-eGDR group (P =0.006, P < 0.001, and P = 0.035, respectively). The eGDR showed a positive relation with APTT (r = 0.142, P < 0.001), a negative relation with FIB (r = − 0.082, P = 0.012), and no correlation with PT (r =0.064, P =0.050) in the all patients. As well as, the eGDR demonstrated a positive relation with APTT (r = 0.173, P < 0.001), a negative relation with FIB (r = − 0.093, P = 0.03), and no relation with PT (r = 0.045, P = 0.300) in the male subgroups. Additionally, this correlation persisted following the adjustment of other factors in multilinear regression analysis. However, the female subgroup demonstrated no correlation among eGDR and PT, APTT or FIB (r = 0.086, P = 0.083, r = 0.097, P = 0.05;r = − 0.058, P = 0.240, respectively).Conclusion: Our study is the first to prove that eGDR demonstrates a correlation with coagulation indexes in T2DM patients. And, this correlation is gender-specific.Keywords: estimated glucose disposal rate, coagulation indexes, type 2 diabetes mellitus